Baby wipes with a mildly acidic, pH-buffering system provided better skin condition compared to cotton washcloth and water in two randomized clinical trials - Robert J. O’Connor; Lisa Bohman; Susanna Brink; Andrew N. Carr; Roger D. Gibb; Ioannis Hatzopoulos; Dirk Van Gysel; Stephanie Christen-Zaech (Global Pediatrics, 2025)
Objectives: Two parallel studies compared the skin health effects of two different baby wipes products to the use of 100 % cotton washcloth and water (WCW). Two wipe products with lotions of 99 % purified water and acidic, pH-buffering systems were tested. The primary objective was to compare the wipes products to the WCW treatment based on severity of erythema, skin barrier integrity (Trans-epidermal Water Loss; TEWL) and pH of skin in the diapered area. Methods: The two studies were prospective, randomized, blinded, parallel-design studies. The first study enrolled 110 babies approximately 3–9 months of age, and the second study enrolled 106 babies up to 36 months of age. The 14-day product use period was preceded by a 7-day washout period. Erythema grading was done at the perianal area, genitals, intertriginous areas, and the buttocks. TEWL and skin pH measurements were done at the genitals and buttocks, with an additional pH measurement taken at the perineum in the second study. Results: Both baby wipe products resulted in significantly lower erythema scores at the perianal region, with Wipe A also being significantly lower at the genital regions compared to WCW. Skin barrier integrity, measured by TEWL, was better for Wipe A at both 7 and 14 days of use with statistical significance achieved at day 14. No TEWL differences were seen for Wipe B versus WCW. Skin pH was significantly lower than WCW at both perianal region and genitals at both 7 and 14 days of use for both wipes, and at Perineum for Wipe B. Conclusion: Based on the results, the baby wipes were shown to be at least as mild as WCW to baby’s skin as measured by lower mean erythema scores and healthy barrier (lower or equal TEWL). The wipes may also provide potential long-term skin health benefits derived from a lower steady-state skin pH.